A interdependência linear do poder calorífico superior em função da análise imediata em materiais lignocelulósicos - Silva, Diego Aleixo da (Universidade Federal de São Carlos, 2019)
The chemical characteristics of lignocellulosic residues influence the quality of biofuel. Higher heating value (PCS) and proximate analysis (volatile matter (TMV), fixed carbon (TCF) and ash content (TC)) give information of the biomass for burning. In literary works it is common for authors to create PCS models based on proximate analysis. However, the linear correlation of these variables is not well demonstrated. Thus, the objective of this research was to analyze the correlation of PCS as a function of the variables of the proximate analysis of different lignocellulosic biomasses. The work was divided into chapters. Chapter 1 presents a literature review on biomass, energy characterization, standard, correlations between PCS and proximate analysis. In Chapter 2 was tested whether there is a difference between the use of different TMV standards. In Chapter 3 a database was created for different pyrolysed biomasses. The bivariate correlations between the PCS and the variables of the proximate analysis were analyzed. With sub-objectives of this chapter residual biomass of Eucalytpus urograndis pyrolyzed in different temperatures (100, 200, 300, 400, 500 and 600 ° C). Ten different lignocellulosic materials were also pyrolyzed at 300 ° C for two hours. In the first sub-objective, the influence of temperature on the energy characteristics of the same material (PCS, TCF, TMV, TCF and Thermal Degradation Time (DTT)) was tested, and in the second, the influence of different materials on the energy characteristics was tested. In Chapter 4, a database for "in natura" biomass was created. The bivariate correlations between the PCS and the variables of proximate analysis were tested. With sub-objectives of this chapter 10 "in natura" biomass were collected and the accuracy of six PCS models of the literature were tested. Energy characteristics were analyzed in addition to bulk density (DG) and peak thermal degradation (PDT). The influences of these parameters were analyzed through a linear correlation matrix. A general conclusion was given in Chapter 5. The results showed that care should be taken when comparing TMV standards, since four different standards resulted in values with different mean values for the same material. Only two standards presented sames values to 5% of siginificance. The literature data showed a linear population correlation between PCS and TCF for different pyrolysed biomasses, however there is no correlation between PCS and TMV. The use of different temperatures in the pyrolysis of a same material improved the energetic characteristics of the material. There was also a positive linear correlation between DTT and PCS and TCF and a negative linear correlation with TMV. For different materials DTT did not correlate with any analyzed variable. Only TCF and PCS presented positive linear correlation when considering different pyrolysed biomasses. It is concluded that there is linear interdependence between the PCS and the variables of the proximate analysis for different "in natura" biomasses. And there is linear interdependence between PCS and TMV for different pyrolysed biomasses under the same conditions.
linear interdependence of the higher heating value regarding proximate analysis in lignocellulosic materials
Keywords: Bioenergia, carbono fixo, teor de materiais voláteis; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL